Identification and standardisation of parameters to improve the understanding of mechanical properties of FFF/FDM/MEX parts - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2023)
Dissertation (MEng(Chemical Engineering))--University of Pretoria, 2023.